OKSANA. NOMINATIVE FIELD OF SUBCONCEPT VALETUDO IN THE LATIN LANGUAGE - Милик, Оксана (Current Issues of Foreign Philology, 2021)
The article is de voted to the investigation of the nominative field of the subconcept VALETUDO in the Latin language, which has a complex character due to the lexical and semantic field, lexical and phraseological field and synonymic series in its composition. The essence of the nominative field in the system of language has been analyzed with the regard to the revealed and ordered set of nominative units; itskerneland prekernel zones, nearandfarperipheries have been defined; the meansofmicrofieldsverbalizationoftheprekerne lzoneofsubconcept VALETUDO as well as the list of linguistic units verbalizing the concept HEALTH have been investigated. It has been defined that nominative field structure of the HEALTH concept is represented as core and pre core zones consisting of some microfields as well as close and distant peripheries of the SALUS, SANITAS, VALETUDO subconcepts. The semantic field of the VALETUDO subconcept has been built up following the principle of semantic proximity/difference from anintegrated seme and frequency of acquiring certain meanings of the concept names. It has been defined that the SALUS, SANITAS, VALETUDO subconcepts share the common slots “being (somatically and/or mentally) healthy” and “providing somatic and/or mental health”. In doing so, the artic le hopes to contribute to the development of the theoretical principles of ancient languages concepts research as well as the aspects of conceptive linguistics, linguistic culturology, axiological linguistics and the investigation of the peculiar language and speech phenomena that enables the scientific community to learn the specific dimensions of ancient speakers’ mode of thinking.